Solomon's secret arts : the occult in the age of enlightenment - Monod, Paul Kléber (Yale University Press, 2013)
The late 17th and 18th centuries are known as the Age of Enlightenment, a time of science and reason. But in this book Paul Monod reveals the surprising extent to which Newton, Boyle Locke, and other giants of rational thought and empiricism also embraced the spiritual, the magical, and the occult. Although public acceptance of occult and magical practices waxed and waned during this period they survived underground, experiencing a considerable revival in the mid-18th century with the rise of new anti-establishment religious denominations.